User Perception to Service Quality (Libqual) in State University Library at Surabaya - Harisanty, Dessy; Khotijah, Siti (Record and Library Journal, 2015)
Services carried out by the library directly and will cause the image library of both positive and negative images. These images create the perception of users and ultimately make an assessment of the library users. In this study the authors wanted to know about the level of user perception on the quality of library services such as affect of service, information control, and library as place. This study uses a quantitative approach that are descriptive and questionnaire data collection techniques with nonrandom sampling with purposive sampling criteria in the library of Institut Teknologi Sepuluh Nopember (ITS), Universitas Airlangga (UNAIR) and the library of the State University of Surabaya (UNESA). Data processing techniques to make the average value in every indicator of service quality. The concept of service quality used is LibQual + â¢ consisting of affect of service, information control, and library as place. The result is that the average value assessment on the performance of the three library users above is good. For UNESA and ITS libraries, order an assessment of the best by the user is a library as place, information control and affect of service. In Unair library, user ratings on the dimensions of the order of the best in a row is a library as place, affect of service, and information control.